GRAIN BOUNDARY AND DISLOCATION MEDIATED DEFORMATION MECHANISMS IN NANOCRYSTALLINE METALS - MITRA, PRO. MANU MITRA (International Journal of Multidisciplinary Research and Studies, 2018)
Nano-crystalline metals performance of defects and mechanisms of plastic deformation and conventional polycrystalline are completely divergent in behavior and its performance. This paper discusses grain boundary and dislocation mediated deformation mechanisms in Nano-crystalline metals. The plots are for burger vectors of single value, Gaussian and uniform characteristics considering various parameters such as elastic constants, plasticity, loading condition, and uncertainty quantification